A geochemical and lithological correlation of lower Jurassic conglomerates in the area surrounding the Lake Baikal rift zone: an improved reconstruction of the region's palaeogeographic and tectonic evolution. Issue 1 (2nd January 2022) - Akulov, N.I.; Melnikov, A.I.; Shtelmakh, S.I.; Akulova, V.V.; Hearn, P.P.
ABSTRACT: This paper describes a study of the lower Jurassic conglomerates in the region around Lake Baikal (Irkutsk and Chita Oblasts, Buryat Republic). The approach used in the study was the analysis of samples from well cores, outcrops, and mine workings. Lithological and geochemical analyses of the conglomerate's matrices suggest that the conglomerates were deposited in a single early Jurassic river paleo-valley, the geological structure of which was later complicated by tectonic processes. The most significant results of this were the formation of the Angara-Selenga imbricate-fan thrust and the Baikal rift basin. The position of the Praselenga River valley was reconstructed for the first time. It is noted that gold-bearing Lower Jurassic conglomerates are represented by mineralogical association resistant to weathering processes formed in the mountain valleys.